Respon Pemikiran Syeikh Nawawi al-Bantani terhadap Ekstremisme dan Intoleransi: Studi Kontekstual Pemikiran untuk Semangat Zaman - M Daffa Isnan Effendi; Rahma Dinda Riyani; Imam Qosthalani; Abdul Fadhil (Yayasan Al-Afif, 2025)
Extremism and intolerance are serious challenges in religious life in the modern era, especially in Indonesia which is home to many different religions and beliefs that often clash with one another. This study aims to analyze how the perspective of an Islamic religious figure named Sheikh Nawawi raises the values ​​of wasathiyah (moderation) in order to create peace and face the challenges of extremism and intolerance. This study uses a qualitative method with a literature study approach that focuses on tracing primary and secondary sources regarding the thoughts of Sheikh Nawawi al-Bantani. The results of the analysis show that Sheikh Nawawi poured many moderate thoughts into his written works such as in the interpretation of Marah Labid, Nihayatuz Zain and Maraqil 'Ubudiyah. The results of this study are expected to be useful data for subsequent researchers in solving the problem of extremism and intolerance, especially through the views of Sheikh Nawawi al-Bantani.